Fenomena Faktor Dominan Tingginya Perceraian di Kabupaten Maros - Abdullah, Abdullah; Aisyah, Nur (Universitas Islam Negeri Alauddin Makassar, 2023)
Divorce becomes the end point of a marriage. Divorce that occurs between married couples is motivated by various reasons. The main problem in this study is the phenomenon of divorce in the Maros community Case Study in Pajukukang Village, Bontoa District, Maros Regency, and how the factors and impacts of divorce in the community. This study aims to find out how the case of divorce problems in the Maros community, especially in Pajukukang Village, Bontoa District, Maros Regency. And what are the factors and impacts of a divorce in the Maros community, Pajukukang Village, Bontoa District, Maros Regency? This research uses qualitative description research methods by collecting data, interviews, documentation, and secondarily, namely literature reviews through books, journals, reports, and internet sites related to the research topic and primarily, collecting information both from communities involved in divorce in Pajukukang Village and KUA and others, or parties and opinions directly from the local community. The results of this study concluded that the phenomenon of divorce in Pajukukanang Society is still high. Divorce problems that were or are not resolved optimally, almost every year there are still those who divorce. Divorce problems are caused by several things, including; Disharmony in the household, moral and moral crisis, strife, infidelity, boredom, early marriage, and loveless marriage.